Desarrollo de un prototipo de cosechadora en vid en estructura de parral - Aguilar, Horacio; Galdeano, Hugo; Rodríguez, Carlos; Bocca, José Carlos; Penisi, O.H.; Chaparro, Heber; Sansó, Oscar; Battistella, Maximiliano (Revista Iberoamericana de Ingeniería Mecánica, 2011)
-